METODE PENYELESAIAN PENYELEWENGAN (AL-TA‘ASSUF) PENGGUNAAN HAK DALAM TRADISI HUKUM ISLAM - Ahmad Arief (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
Al-Ta'assuf in the use of rights is a terminology in Islamic law which by the experts usul al-fiqh used as one of the indicators in doing istinbat al-hukm (the determination of the law). The method of settling the use of rights is the most obvious evidence that Islam is not a religion of terror. The fulfillment of the right and anticipation of misuse on every human right has been established in the method since the time of the Prophet, reinforced by the results of the legal examination of the four Imams of the Mazhab when they performed a law.